2022
DOI: 10.3390/molecules28010296
|View full text |Cite
|
Sign up to set email alerts
|

H3PO4/KOH Activation Agent for High Performance Rice Husk Activated Carbon Electrode in Acidic Media Supercapacitors

Abstract: H3PO4/KOH combined solution is proposed as a new effective activation agent for activated carbon production from rice husk. Several activated carbon samples were produced by using different volumes of the utilized acid and alkali individually, in addition to the combined solution. FTIR results indicated that the mixed agent partially decomposed the chemical compounds on the rice husk char surface, resulting in an increase in the surface area. Moreover, XRD and EDS analyses showed the presence of a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…According to Liou et al 26 , around 84% of the metallic impurities could be extracted by refluxing the graphitized rice husk with 3 N HCl at 100 °C for 1 h. As can be concluded from Fig. 1 B, utilizing of phosphoric acid after the carbonization process resulted in dissolution the metallic impurties from the produced char which in consistient with the other reports 42 , 43 . Accordingly, it can be claimed that, to maintain some metallic compounds in the rice husk-originated activated carbon, it is recommended to utlize the acid before the carbonization step.…”
Section: Resultsmentioning
confidence: 72%
“…According to Liou et al 26 , around 84% of the metallic impurities could be extracted by refluxing the graphitized rice husk with 3 N HCl at 100 °C for 1 h. As can be concluded from Fig. 1 B, utilizing of phosphoric acid after the carbonization process resulted in dissolution the metallic impurties from the produced char which in consistient with the other reports 42 , 43 . Accordingly, it can be claimed that, to maintain some metallic compounds in the rice husk-originated activated carbon, it is recommended to utlize the acid before the carbonization step.…”
Section: Resultsmentioning
confidence: 72%
“…64,65 Furthermore, the metallic potassium interacted with the cellulose cell wall, extending the space between carbon atomic layers, which was the driving force for generating increased total pore volume. 62 On the contrary, activated and carbonized carbon from NaOH-treated jute were noticed less porous than that of untreated jute. In pretreatment with NaOH, hemicellulose and lignin were removed, and the cross section became denser, resulting in a less porous structure.…”
Section: Resultsmentioning
confidence: 95%
“…The general mechanism of activating carbon with chemical agents such as H 3 PO 4 and KOH relies on the destruction of cellulose structures followed by char formation and aromatization of the carbon skeleton. 62 It was observed that a honeycomb-like porous structure was created after chemical activation. The blocked pores in carbonized carbon were opened after chemical activation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the interplay between metallic potassium and the carbon matrix widens the gap between carbon atomic layers, raising the overall pore volume. whereas phosphoric acid exhibits an intriguing performance as an activating agent because of its propensity to adhere to biomaterials and break them down thereafter. The impact of various activation temperatures and activating agents on the electrochemical performance and stability of coconut-husk-derived electrodes and their long-term LED powering has not been the subject of any of the current investigations.…”
Section: Introductionmentioning
confidence: 99%